PENINGKATAN KESEHATAN MASYARAKAT DI DUSUN NGLAMPU DENGAN PALANG DAPUR - Madita, Vincentia Ganesi; Sitio, Jessica Christy; Octavianus, Agatha Riona (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Dusun Nglampu is located in Desa Pucanganom, Kecamatan Srumbung, Kabupaten Magelang. People have difficulty to access health service because of expensive medication in hospital and limited operation time in puskesmas. Commonly, people do not know how to process herbs for medication. Consequently, they do not have alternative medication which is accessible. In this program, a guideline of the use of herbs as medicine is packed in a book called